Ecological state assessment of the Novik Bay (Peter the great Bay, Sea of Japan) by biomonitoring methods During Summer 2024 - A.D., Pelekh; T.V., Boychenko; A.A., Shestera; Yu. A., Galysheva (Edelweiss Applied Science and Technology, 2025)
The content and distribution of indicator groups of microorganisms were studied. Biotesting of water and aqueous extracts from bottom sediments of Novik Bay (Russky Island, Peter the Great Bay, Sea of Japan) was conducted. It was established that at the time of observation, the waters of the bay belonged to the category of α-β-mesosaprobic, and the obtained values of the oligotrophic index indicated the accumulation of easily accessible organic matter. The biological pollution of water was indicated by a high number of bacteria of the sanitary indicator group, exceeding permissible standards, and the activity of plant communities was indicated by the presence of large quantities of indicators of phenolic contamination of the environment. Nickel-resistant bacteria stood out in terms of numbers and distribution among the groups of metal-resistant microorganisms, which is due to the combustion of hydrocarbon fuels, confirming the widespread distribution of oil-oxidizing microorganisms. The bioassay showed that water and aqueous extracts from bottom sediments had a depressing effect on the Ph. tricornutum culture in the acute experiment, indicating the presence of pollutants in the environment that are toxic to microalgae. None of the water samples showed any toxic effects on the microalgae culture in the chronic experiment. However, bioassay of aqueous extracts from the soil revealed a stimulating effect, most likely due to the accumulation of organic matter in the bay's soils.